MBCL-25. OUTCOME OF CHILDREN WITH MEDULLOBLASTOMA AT TERTIARY CARE HOSPITAL IN PAKISTAN. Issue 2 (22nd June 2018) - Hamid, Syed Ahmer; Dawson, Maria Idrees; Khan, Rahil; Ashraf, Muhammad Shamvil; Qaddoumi, Ibrahim
Abstract: BACKGROUND: Brain tumours have been attributed as the leading cause of childhood cancer mortality and major problems faced by developing countries in term of poor survival rate. MATERIALS AND METHODS: A retrospective chart review. Total number of 63 patients, ranging from 0 - 18 years, with medulloblastoma out of 341 patients with brain tumor at Indus Hospital. Data collected from June 1997 to November 2016. The data analyzed using SPSS 21 to calculate the survival rate of patients and frequency of outcomes. RESULTS: The total percentage of children with medulloblastoma is 19% among all children with brain tumors in our centre 63/341. Average age of presentation was 8 years. Male to female ratio was 2:1. The most common symptom was headache (20%) followed by vomiting 19%. Time interval from the first symptom till surgery was on average 4 months with a maximum delay of 17 months. A significant percentage of children presented with metastatic disease 38%. Leptomeningeal spread was the most common site (23%). Only 47/63 were risk stratified (75%). Among them standard risks were 19% and high risk were 56%. Among the whole cohort 42 (67%) were actively treated .23/42 (55%) completed treatment, 12/42(29%) are alive and off treatment. 8/42(19%) are on treatment at the time of analysis. Outcome in children who were actively treated was 20/42 (48%).Overall outcome in whole cohort is 32%. CONCLUSION: Significant delay in the diagnosis, poor socio-economic status, advance disease, abondonment are major challenges. Developing multidisciplinary services, dedicated neuro-oncological expertise will help in improving the overall outcome.